2008
DOI: 10.1093/ndt/gfm815
|View full text |Cite
|
Sign up to set email alerts
|

Anaemia and congestive heart failure early post-renal transplantation

Abstract: Modification of risk factors may improve anaemia management post transplantation. Reducing the prevalence of anaemia may in turn reduce the incidence of CHF-these observations support the need for clinical trials to determine how anaemia management may impact CHF incidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
1
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 33 publications
0
11
1
2
Order By: Relevance
“…The predictors of early HF following kidney transplant have not been well studied. In a recent study of 132 kidney transplant recipients, early HF was common and was associated with post-transplant anemia, allograft dysfunction, duration of dialysis prior to transplant, and degree of pretransplant LVH 22. Of note, in our study sample the relative rise in HF risk early after transplant was smaller with living compared to deceased donor transplantation across BMI strata, possibly reflecting superior early graft function in this cohort.…”
Section: Discussionmentioning
confidence: 48%
“…The predictors of early HF following kidney transplant have not been well studied. In a recent study of 132 kidney transplant recipients, early HF was common and was associated with post-transplant anemia, allograft dysfunction, duration of dialysis prior to transplant, and degree of pretransplant LVH 22. Of note, in our study sample the relative rise in HF risk early after transplant was smaller with living compared to deceased donor transplantation across BMI strata, possibly reflecting superior early graft function in this cohort.…”
Section: Discussionmentioning
confidence: 48%
“…It is possible that the dominant influence of some factors prevented the detection of factors that are of less prognostic importance. The literature showed very confusing data on the role of various factors in poor outcomes in renal patients [7][8][9][10][11][12][13][29][30][31][32][33][34][35]. These discrepancies may be related to differences in population characteristics, sampling size, observation time, method of analysis and the impact of confounding covariates on the outcome of multivariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies have reported anatomic and functional abnormalities in kidney transplant recipients,10)11) but the effects of kidney transplant on LV rotation, twist and torsion has never been investigated. Therefore, we employed velocity vector imaging to assess LV rotation, twist and torsion pre and post kidney transplant in end stage renal disease patients without myocardial infarction.…”
Section: Introductionmentioning
confidence: 99%